Local Government Innovations In Optimizing The Sinyaman Dinsosku Website Through Digital-Based Services At The Kuningan Social Affairs Office - Alfita Apriliana; Yanto Heryanto (ann4publisher@gmail.com, 2026)
Background. The “Sinyaman Dinsosku” website was launched by the Kuningan Regency Social Affairs Office to optimize digital-based public services. This innovation has benefited the community, as services that previously took days to complete can now be completed in minutes or hours. Aims. The objective of this study is to identify the barriers and corresponding mitigation strategies, drawing on Everett M. Rogers' (2003) innovation theory in his book *Diffusion of Innovations*, which encompasses the following characteristics: Relative Advantage, Compatibility, Complexity, Trialability, and Observability. Methods. The method used in this study is a descriptive qualitative approach implemented through observation, interviews, and documentation with the Head of the Social Empowerment and Poverty Alleviation Division of the Kuningan Regency Social Services Agency, the Social Services Agency Operations Manager, the Village Coordinator, and the residents of Linggamekar Village, Kuningan Regency. Conclusion. Research indicates that the “Sinyaman Dinsosku” website has been effectively implemented, both in terms of time and cost efficiency, and significantly simplifies the public's process of managing administrative applications for social assistance. Although this website has demonstrated adequate accessibility, several challenges hinder the optimization of public services, including vulnerability to hacking, internet connectivity disruptions, uneven distribution of human resources (HR), and miscommunication among the Social Affairs Office, village operators, and the public, which affect the effectiveness of e-government.